Plasmonic Internal Photoemission for Accurate Device In Situ Measurement of Metal‐Organic Semiconductor Injection Barriers. (3rd May 2014) - Dhanker, Rijul; Chopra, Neetu; Giebink, Noel C.
<x xml:space="preserve">Abstract</x> Current injection in organic semiconductors remains difficult to predict due in large part to the challenge of characterizing the contact energy barrier and interface density of states directly in organic electronic devices. Here, resonant coupling to surface plasmon polariton modes of a metal contact is demonstrated as a means to carry out internal photoemission (IPE) accurately in disordered organic semiconductor devices and enable direct measurement of the contact injection barrier by isolating true IPE from spurious sub‐gap organic photoconductivity. The substantial increase in sensitivity afforded by resonant coupling enables measurement in the low‐field injection regime where deviation from the standard Fowler prediction is explained quantitatively by the existence of a broad distribution of interface states. This technique is broadly applicable to metals and surface treatments commonly used in organic light emitting diodes, thin film transistors, and photovoltaics, and should therefore provide a quantitative basis to understand and model current injection in these devices over their entire operational lifetime.